Preferences of German melanoma patients for interferon (IFN) α-2b toxicities (the DeCOG "GERMELATOX survey") versus melanoma recurrence to quantify patients' relative values for adjuvant therapy. Issue 46 (November 2016) - Kaehler, Katharina C.; Blome, Christine; Forschner, Andrea; Gutzmer, Ralf; Haalck, Thomas; Heinzerling, Lucie; Kornek, Thomas; Livingstone, Elisabeth; Loquai, Carmen; Maul, Lara Valeska; Lang, Berenice M.; Schadendorf, Dirk; et al.
Abstract : Abstract: Currently interferon alfa-2b (IFNα-2b) is an approved adjuvant drug for high-risk melanoma patients that leads to an improvement in disease-free survival (DFS). However, it is unclear whether it also impacts overall survival. Widespread use of adjuvant high-dose IFNα has been tempered by its significant toxicity and its limited efficacy. Current therapeutic strategies like immune checkpoint blockade or targeted therapy may also be useful in the adjuvant setting. Therefore, it is important to weigh the trade-offs between possible side effects and therapeutic benefit. We assessed patient utilities for health states associated with IFN therapy. Utilities are measures of preference for a specific health state on a scale of 0 (death) to 1 (perfect health). Utilities were determined for health states associated with adjuvant IFN among 130 German low-risk melanoma patients using the standard gamble technique. Four IFNα-2b toxicity scenarios and the following 3 posttreatment outcomes were assessed: disease-free health and melanoma recurrence (with or without previous use of IFNα-2b) resulting in cancer death. Patients were asked to trade-off the improvement in 5-year DFS and the IFN-related side effects. Utilities for melanoma recurrence (mean 0.60) were significantly lower than for all IFNα-2b toxicity scenarios (mean 0.81–0.90). Patients were willing to tolerate mild-to-moderate and severe toxicity for a 50% and 75% chance of 5-year DFS, respectively. Both utilities and threshold benefits were mostly independent from patient characteristics like gender, income, and social situation. Significant impact was only observed by age and previous personal experience with cancer. On average, German patients were willing to trade even severe IFNα-2b toxicity for reducing the rate of melanoma recurrence. This result points out the importance of a relapse-free survival for melanoma patients. The utilities measured in our study can be applied to decision-making processes in clinical trials of new adjuvant drugs.